KEPUTUSAN PEMBELIAN MELALUI ONLINE MARKETPLACE TOKOPEDIA - Nadhira Safa Kirana (2021)
The high competition of online marketplace in Indonesia encourages each online marketplace to be able to create advantages over its competitors. Tokopedia is one of the online markets with the highest number of website visitors in Indonesia, but Tokopedia still has some problems. The purpose of this study was to determine and analyze the influence of beliefs, lifestyles, also sales promotions on purchasing decisions in online marketplace Tokopedia. The sample in this study were consumers who have made purchases at Tokopedia at least 2 times and are located in South Jakarta as many as 100 respondents with purposive sampling technique as the sampling technique. The data in this study were obtained from a questionnaire and measured using a Likert scale. The data analysis technique in this research is descriptive and inferential data analysis technique. According to the results of data processing through t-statistics on SmartPLS, the results show that trust has a significant effect on purchasing decisions, lifestyle has a significant effect on purchasing decisions, and sales promotions have a significant effect on purchasing decisions.